Quality changes in surimi sausages stored at 12+2 C. - Madamba, Alejandro Benjamin R. (College of Fisheries, University of the Philippines, 1993)
The effect of smoking treatment and fish species (big-eyed snapper, priacanthus tayenus and squid, loligo sp.) on the acceptability and shelf life of surimi sausages was determined through physic-chemical and microbial tests as well as sensory evaluation of quality. The physic chemical characteristics of the surimi sausages were analyzed using the procedures of the determination of percent expressible moisture (%EM), folding test, and pH whereas the microbial load was analyzed using total plate count. Likewise, the surimi sausages were evaluated sensorily using a descriptive scorecard for the determination of changes in texture, flavor, odor appearance and general acceptability. Results form this study reveal that , in general, smoking treatment improves the acceptability of surimi sausages: smoked surimi sausages from both 100% fish flesh and 50%/50% squid/fish flesh are more preferred than the unsmoked samples. Likewise, smoking treatment results to better quality surimi sausages as exhibited by better texture, higher gel strength and lower microbialo load of the smooked samples. Analyses of results further indicate that fish surimi and squid/ fish surimi sausages can be kept in at 12~c degree C for 18 days for the smoked samples and 15 days for the unsmoked samples. In general, this study shows that the applicability of the surimi process technology in the production of both fish and fish/squid sausages wherein squid surimi can still result to quality product.